Ambient temperature and subsequent COVID-19 mortality in the OECD countries and individual United States - Christophi, Costas A.; Sotos-Prieto, Mercedes; Lan, Fan Yun; Delgado-Velandia, Mario; Efthymiou, Vasilis; Gaviola, Gabriel C.; Hadjivasilis, Alexandros; Hsu, Yu-Tien; Kyprianou, Aikaterini; Lidoriki, Irene; Wei, Chih-Fu; Rodriguez-Artalejo, Fernando; et al. (My University, 2021)
Epidemiological studies have yielded conflicting results regarding climate and incident SARS-CoV-2 infection, and seasonality of infection rates is debated. Moreover, few studies have focused on COVD-19 deaths. We studied the association of average ambient temperature with subsequent COVID-19 mortality in the OECD countries and the individual United States (US), while accounting for other important meteorological and non-meteorological co-variates. The exposure of interest was average temperature and other weather conditions, measured at 25 days prior and 25 days after the first reported COVID-19 death was collected in the OECD countries and US states. The outcome of interest was cumulative COVID-19 mortality, assessed for each region at 25, 30, 35, and 40 days after the first reported death. Analyses were performed with negative binomial regression and adjusted for other weather conditions, particulate matter, sociodemographic factors, smoking, obesity, ICU beds, and social distancing. A 1 °C increase in ambient temperature was associated with 6% lower COVID-19 mortality at 30 days following the first reported death (multivariate-adjusted mortality rate ratio: 0.94, 95% CI 0.90, 0.99, p = 0.016). The results were robust for COVID-19 mortality at 25, 35 and 40 days after the first death, as well as other sensitivity analyses. The results provide consistent evidence across various models of an inverse association between higher average temperatures and subsequent COVID-19 mortality rates after accounting for other meteorological variables and predictors of SARS-CoV-2 infection or death. This suggests potentially decreased viral transmission in warmer regions and during the summer season.
Keywords: Air Pollutants; Climate; Comorbidity; COVID-19; Global Health; Hot Temperature; Organisation for Economic Co-Operation and Development; Particulate Matter; Seasons; United States